PRODUKSI DAN KARAKTERISASI SENYAWA LIQUID VOLATILE MATTER AMPAS SAGU MENGGUNAKAN METODE PIROLISIS DAN GAS CHROMATOGRAPHY - Muhammad Jahiding; W.O.S. Ilmawati; M. Burhan (Universitas Halu Oleo, 2015)
This study investigated the effect of pyrolysis temperature on the volume and the building blocks of Liquid Volatile Matter sago dregs. Sago dregs obtained from Sampara Village, District Sampara, Konawe, Southeast Sulawesi. The dried sago dregs, then dipirolisis at varied temperatures of 400 ℃, 500 ℃, 600 ℃ and 700 ℃. Pyrolysis process each starting at 27 ℃ and performed for 25 minutes. One of the products of pyrolysis residue sago is condensed smoke. The smoke that had condensed liquid is called volatile matter (LVM). Sago dregs LVM volume was measured using a measuring cup and its constituent compounds were characterized using GC-MS Gilent. When the pyrolysis temperature of 400 ℃, 500 ℃ and 600 ℃, sago dregs LVM volume increases. Meanwhile the pyrolysis temperature of 700 ℃ sago dregs LVM volume decreases. GC-MS characterization results indicate that the pyrolysis temperature of 500 ℃ to produce compounds most. While the pyrolysis temperature of 600 ℃ and 700 ℃ several compounds disappear. LVM compound sago dregs dominated by ammonia.